Pengaruh Literasi Keuangan, Fear of Missing Out (FOMO), dan Influencer Marketing terhadap Keputusan Penggunaan Buy Now Pay Later (BNPL) pada Generasi Z di Kabupaten Dompu - Dwi Wulandari; Mulyati Mulyati; Rizky Ramadhan (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
This study examines the influence of financial literacy, Fear of Missing Out (FOMO), and influencer marketing on Generation Z's decision to use Buy Now Pay Later (BNPL) services in Dompu Regency. The rapid development of financial technology has encouraged the widespread adoption of BNPL as an alternative digital payment method, particularly among young consumers. However, the increasing use of this service also raises concerns regarding financial decision-making and consumer behavior. This research employed a quantitative approach using a survey method involving 100 Generation Z respondents selected through purposive sampling. Data were collected using a structured questionnaire with a five-point Likert scale and analyzed using multiple linear regression. The findings indicate that financial literacy has a positive and significant effect on BNPL usage decisions. Likewise, FOMO significantly influences individuals' decisions to utilize BNPL services, while influencer marketing also demonstrates a positive and significant contribution to users' decisions. Simultaneously, the three independent variables significantly affect BNPL usage decisions, explaining 27% of the variance in the dependent variable. These findings suggest that financial knowledge, psychological factors, and social influence collectively shape Generation Z's financial behavior. Therefore, strengthening financial literacy and promoting responsible use of digital financial services are essential to encourage more informed and sustainable financial decision-making.